2019
DOI: 10.1038/s41598-019-56232-1
|View full text |Cite
|
Sign up to set email alerts
|

The Rarity of Depth Refugia from Coral Bleaching Heat Stress in the Western and Central Pacific Islands

Abstract: Some researchers have suggested that corals living in deeper reefs may escape heat stress experienced by shallow corals. We evaluated the potential of deep coral reef refugia from bleaching stress by leveraging a long record of satellite-derived sea surface temperature data with a temporal, spatial, and depth precision of in situ temperature records. We calculated an in situ stress metric using a depth bias-adjusted threshold for 457 coral reef sites among 49 islands in the western and central Pacific Ocean ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Projected warming rates and the existing "community thermal safety margin" (the inherent buffer against temperature anomalies based on thermal sensitivity of constituent species; Bruno et al, 2018) may vary with the latitude among ecoregions and MCEs. However, what constitutes the safe thermal range for MCEs is not well understood, and it may be lower than that for shallow-water communities, especially in tropical coasts with a unithermal water column (the same temperature from the surface to the sea floor at mesophotic depths) (Venegas et al, 2019). A recent study showed that thermal stress events can penetrate to the depths where MCEs are found (Frade et al, 2018;Venegas et al 2019), meaning the twilight zone may not represent a thermal refuge for corals.…”
Section: Key Features Of Mcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Projected warming rates and the existing "community thermal safety margin" (the inherent buffer against temperature anomalies based on thermal sensitivity of constituent species; Bruno et al, 2018) may vary with the latitude among ecoregions and MCEs. However, what constitutes the safe thermal range for MCEs is not well understood, and it may be lower than that for shallow-water communities, especially in tropical coasts with a unithermal water column (the same temperature from the surface to the sea floor at mesophotic depths) (Venegas et al, 2019). A recent study showed that thermal stress events can penetrate to the depths where MCEs are found (Frade et al, 2018;Venegas et al 2019), meaning the twilight zone may not represent a thermal refuge for corals.…”
Section: Key Features Of Mcesmentioning
confidence: 99%
“…However, what constitutes the safe thermal range for MCEs is not well understood, and it may be lower than that for shallow-water communities, especially in tropical coasts with a unithermal water column (the same temperature from the surface to the sea floor at mesophotic depths) (Venegas et al, 2019). A recent study showed that thermal stress events can penetrate to the depths where MCEs are found (Frade et al, 2018;Venegas et al 2019), meaning the twilight zone may not represent a thermal refuge for corals. Therefore, it is possible that the tolerance of MCEs to certain environmental changes, such as shifts in temperature and pH, is narrower than that of shallow-water coral ecosystems (Shlesinger et al, 2018).…”
Section: Key Features Of Mcesmentioning
confidence: 99%
“…Venegas et al 2019). Such spatial variability has been studied on Jarvis island Venegas et al 2019), and found to vary by up to 0.5°C degrees around the east side of the island, and up to 2°C between the east and the west (where upwelling from the EUC occurs). The cores used in this analysis were selected opportunistically, and although in situ logger data has been collected at several locations on Jarvis island, the closest logger to colony J1222 was ~700 m away.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the complex bathymetry and resultant hydrodynamics of coral reefs, these environments are subject to systematic temperature variability on kilometer to meter scales (e.g. Venegas et al 2019). Such spatial variability has been studied on Jarvis island Venegas et al 2019), and found to vary by up to 0.5°C degrees around the east side of the island, and up to 2°C between the east and the west (where upwelling from the EUC occurs).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, it has been assumed that coral bleaching is mitigated in deeper waters, relating to the cooler temperatures, and may serve as a reserve for shallow coral restoration [101]. More recent research, however, has shown extensive bleaching at deeper reefs [102], even into the mesophotic zone at up to 60 m depth [103,104]. Explanations clarifying this counterintuitive inconsistency include tidal mixing with shallow heated waters [105], anomalous deep-water currents [102], host nutrient starvation [103], and the possible predominance of more stress-tolerant corals at shallow sites [29,106].…”
Section: Coral Bleachingmentioning
confidence: 99%